THEOLOGICAL PERSPECTIVES ON DEVELOPMENT: COMPARING ROMAN CATHOLIC, ECUMENICAL AND EVANGELICAL POSITIONS - Kroeck, T. (Acta Theologica, 2021)
Since the middle of the 20th century, Christian churches have been involved internationally in development activities. In recent years, international agencies and national governments have recognised the role of religions in international development. This article reviews theological views on international development. For this purpose, official documents of the Roman Catholic Church, the ecumenical movement and the World Evangelical Alliance/Lausanne Movement are compared regarding concepts of development and its role in the mission of the Church and views on the world and humankind, actions and actors of development and eschatology. The study finds wide agreement in many aspects, but also some differences between the theological traditions. It discusses theological aspects that are relevant for the praxis of Christian development work and identifies issues that may need further research.